Analysis of virtual classrooms in the education sector: A systematic review of literature - Melchor Giraldo, Alberto Rafael; Morales Sanchez, Marco Alejandro; Sierra Liñan, Fernando Alex; Moquillaza Henriquez, Santiago Domingo (LACCEI, 2025)
Abstract– Following the lessons learned during the COVID-19 pandemic, many education organizations decided to implement virtual classrooms for the delivery of their services, and they have proven to be a beneficial contribution to the education sector. However, this technology still presents many challenges and barriers to its proper integration. In this sense, it is important to analyze the scope and impact of virtual classrooms in this sector, as well as other technologies that, in conjunction with virtual classrooms, can help provide quality education. This systematic review provides an analysis of the impact of virtual classrooms in the education sector to improve the delivery of education through technology. A total of 437 articles were analyzed, of which 57 were considered relevant to the research. In addition, they were classified to answer questions related to the benefits of use, implementation and development trends and technologies most used in the management of virtual classrooms. In this sense, with 28.57%, it was identified that the main advantage of the use of virtual classrooms is that it improves the learning process. Likewise, LMS platforms, artificial intelligence, immersive environments and videoconferencing were the most used technologies in the educational sector found with 43.75%, 18.75%, 15.63% and 21.88% respectively. Finally, it was found that the most used trend is the use of methodological approaches with 28.57%. This trend is followed by others such as educational inclusion, evaluation of external factors and use of digital competencies in virtual environments.